U–Pb zircon geochronology of the Hida gneiss and granites in the Kamioka area, Hida Belt. (29th March 2019) - Takehara, Mami; Horie, Kenji
Abstract: A new U–Pb dating and oxygen isotope analysis of zircons collected from a granitic mylonite and an undeformed granite in the Kamioka area, in the Hida Belt of southwest Japan, was conducted using a sensitive high‐resolution ion microprobe (SHRIMP) to restrict the timing of the mylonitization in the Funatsu Shear Zone, which is situated on the eastern and southeastern margins of the Hida Belt. Here, undeformed granite intrudes into the granitic mylonite deformed by mylonitization in the Funatsu Shear Zone. The granitic mylonite and the undeformed granite yielded U–Pb zircon ages of 242.6 ±1.9 Ma and 199.1 ±1.9 Ma, respectively. The granitic mylonite and the undeformed granite also yielded zircon oxygen isotope ratios (δ 18 OVSMOW ) of 7.74 ±0.37 ‰ and 5.74 ±0.17 ‰, which suggests that these rocks are derived from different magmas. Therefore, the timing of the mylonitization in the Funatsu Shear Zone is constrained to be at least 242.6–199.1 Ma, which is consistent with other data from the Tateyama area. The U–Pb zircon ages of the banded gneiss in the Kamioka area also reveals that the protolith is a sedimentary rock deposited at approximately 256 Ma, and regional metamorphism occurred at 245.0 ±6.6 Ma, which indicates that the mylonitization in the Funatsu Shear Zone occurred after the metamorphism in the Hida Belt. These geochronological and geochemical data give new insight into the relationship between the Hida Belt and the eastern margin of the Asian continent: the geochronological and geochemical data in this study support the possibility that the Funatsu Shear Zone is comparable with the Cheongsan Shear Zone located at the center of the Ogcheon Belt on the Korean Peninsula. Abstract : A new U–Pb dating and oxygen isotope analysis of zircons collected from a granitic mylonite and an undeformed granite in the Kamioka area, in the Hida Belt of southwest Japan, was conducted using a sensitive high‐resolution ion microprobe (SHRIMP) to restrict the timing of the mylonitization in the Funatsu Shear Zone, which is situated on the eastern and southeastern margins of the Hida Belt. The granitic mylonite and the undeformed granite yielded U–Pb zircon ages of 242.6 Ma ±1.9 Ma and 199.1 Ma ±1.9 Ma, respectively, which suggests that the timing of the mylonitization in the Funatsu Shear Zone is constrained to be at least 242.6–199.1 Ma. The U–Pb zircon ages of the banded gneiss in the Kamioka area also reveals that the protolith is a sedimentary rock deposited at around 256 Ma, and regional metamorphism occurred at 245.0 Ma ±6.6 Ma, which indicates that the mylonitization in the Funatsu Shear Zone occurred after the metamorphism in the Hida Belt. Abstract : 飛騨帯神岡地域には，船津せん断作用で変形した花崗岩質マイロナイト，それに貫入する非変形の花崗岩，および飛騨変成作用による縞状片麻岩が産する.これらの岩石のジルコンを対象に，高精度高分解能イオンマイクロプローブ(SHRIMP)を用いて，ウラン−鉛(U‐Pb)年代測定と酸素同位体比の分析を行った.非変形の花崗岩は，船津せん断作用で変形した花崗岩質マイロナイトに貫入しており，ジルコンのU‐Pb年代値はそれぞれ，199.1 Ma ±1.9 Ma及び242.6 Ma ±1.9 Maである.また，ジルコンの酸素同位体比(δ 18 OVSMOW )はそれぞれ、7.74 ‰ ±0.37 ‰，5.74 ‰ ±0.17 ‰であり，異なるソースに由来することが示唆される.これらの年代より，船津せん断帯の活動時期は，242.6 Maから199.1 Maの間に限定され，これは，立山地域における年代学的制約と整合的である.また，神岡地域の縞状片麻岩の原岩は堆積岩であり，U‐Pbジルコン年代値は245.0 Ma ±6.6 Maの広域変成作用を示す.よって、飛騨変成作用は船津せん断帯の変形作用よりも前に起こったことが示唆される.